The single‐cell transcriptional landscape of lung carcinoid tumors. Issue 12 (16th March 2022) - Bischoff, Philip; Trinks, Alexandra; Wiederspahn, Jennifer; Obermayer, Benedikt; Pett, Jan Patrick; Jurmeister, Philipp; Elsner, Aron; Dziodzio, Tomasz; Rückert, Jens‐Carsten; Neudecker, Jens; Falk, Christine; Beule, Dieter; et al.
Abstract: Lung carcinoid tumors, also referred to as pulmonary neuroendocrine tumors or lung carcinoids, are rare neoplasms of the lung with a more favorable prognosis than other subtypes of lung cancer. Still, some patients suffer from relapsed disease and metastatic spread. Several recent single‐cell studies have provided detailed insights into the cellular heterogeneity of more common lung cancers, such as adeno‐ and squamous cell carcinoma. However, the characteristics of lung carcinoids on the single‐cell level are yet completely unknown. To study the cellular composition and single‐cell gene expression profiles in lung carcinoids, we applied single‐cell RNA sequencing to three lung carcinoid tumor samples and normal lung tissue. The single‐cell transcriptomes of carcinoid tumor cells reflected intertumoral heterogeneity associated with clinicopathological features, such as tumor necrosis and proliferation index. The immune microenvironment was specifically enriched in noninflammatory monocyte‐derived myeloid cells. Tumor‐associated endothelial cells were characterized by distinct gene expression profiles. A spectrum of vascular smooth muscle cells and pericytes predominated the stromal microenvironment. We found a small proportion of myofibroblasts exhibiting features reminiscent of cancer‐associated fibroblasts. Stromal and immune cells exhibited potential paracrine interactions which may shape the microenvironment via NOTCH, VEGF, TGFβ and JAK/STAT signaling. Moreover, single‐cell gene signatures of pericytes and myofibroblasts demonstrated prognostic value in bulk gene expression data. Here, we provide first comprehensive insights into the cellular composition and single‐cell gene expression profiles in lung carcinoids, demonstrating the noninflammatory and vessel‐rich nature of their tumor microenvironment, and outlining relevant intercellular interactions which could serve as future therapeutic targets. Abstract : What's new? Single‐cell transcriptomic profiling has been used as a powerful tool to dissect tumor cellular heterogeneity in conventional subtypes of lung cancer. The characteristics of lung carcinoids on the single‐cell level are yet to be determined. Here, the authors found that the single‐cell transcriptomes of carcinoid tumor cells reflect intertumoral heterogeneity and clinicopathological features. They provide comprehensive insights into the cellular composition and specific features of the lung carcinoid tumor microenvironment and potential intercellular interactions. The study uncovers new aspects of lung carcinoid tumor biology and may lead to the identification of novel biomarkers and therapeutic targets.